The Role of Gender on Women's Participation in the Labour Force in China: A Comparative Study Between Patriarchal Culture and Modernization - Krisnadi, Tasya Widya (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to explore the influence of gender roles influenced by patriarchal culture and modernization on women's participation in the workforce in China. Using the literature review method, this study critically examines relevant previous studies to identify key factors affecting women's participation in the labor force and their implications for economic and social development in China. The results show that China's deep-rooted patriarchal culture has shaped gender stereotypes and social norms that limit women's role in the public sphere, including in the labor market. However, China's modernization process has driven social and economic transformations that have opened up opportunities for women to participate in the workforce. This research also reveals the disparities between urban and rural areas, as well as differences in education levels that affect women's access to and participation in the labor force. This research contributes to a deeper understanding of the dynamics of gender roles and their influence on women's labor force participation in China. The findings of this study can provide more effective policy recommendations to improve gender equality and empower women in economic and social development in China.